Potential impacts of climate change on plant diversity of sary-chelek biosphere reserve in Kyrgyzstan - (:unkn) unknown (Springer International Publishing, 2018)
The Sary-Chelek Nature Reserve established in 1959 with an area of 239 km2 and declared as a UNESCO-MAB Biosphere Reserve in 1978 is located on the southeast-facing slope of the northern Chatkal Range in central Jalalabad province. It is centered around the scenic Sary-Chelek Lake. The mountains immediately surrounding the lake abound in exceptionally diverse flora and fauna, what may be the widest variety found in the Tian Shan. The area is spread over varied ecosystems and habitats, which include the forests of spruce and juniper together with the forests of wild fruits and nuts and riparian forests as well as a variety of steppe and meadow ecosystems. The total number of vascular plants growing in the study area is 668 taxa. These belong to 69 families and 313 genera. 531 taxa are from the dicotyledonous group, whereas 127 taxa are from the monocotyledonous group. This chapter presents an analysis of the potential impacts of climate change on plant diversity of this biosphere reserve. © Springer Nature Switzerland AG 2018.
Keywords: Biodiversity; Biosphere reserve; Climate change; Sary-Chelek